2018
DOI: 10.1038/s41598-017-18435-2
|View full text |Cite
|
Sign up to set email alerts
|

Ecological plasticity in the gastrointestinal microbiomes of Ethiopian Chlorocebus monkeys

Abstract: Human activities can cause habitat degradation that may alter the types and quality of available food resources and thus influence the microbiomes of wild animal populations. Furthermore, seasonal shifts in food availability may cause adaptive responses in the gut microbiome to meet the need for different metabolic capabilities. Here, we demonstrate local-scale population structure in the gastrointestinal microbiotas of Chlorocebus monkeys, in southern Ethiopia, in response to varying degrees of human encroach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 51 publications
5
36
0
Order By: Relevance
“…In general, we found that microbial OTUs clustered according to location and that prokaryotic α diversity was highest in the most pristine site and significantly lower in sites with a history of disturbance. Within the primate clade, similar patterns have been described in the Chlorocebus genus (Trosvik et al, ), Alouatta pigra (Amato et al, ), Lemur catta (Bennett et al, ), and Procolobus gordonorum (Barelli et al, ). GM robustness to habitat disturbance has been reported in parrots ( Strigops habroptilus ; see Perry, Digby, & Taylor, ), but other taxa, including frogs ( Fejervarya limnocharis ; see Chang, Huang, Lin, Huang, & Liao, ), jackals ( Canis mesomelas ; see Menke et al, ), and swan geese ( Anser cygnoides ; see Wu et al, ) show that populations in disturbed habitats exhibit distinct GMs relative to pristine habitat counterparts.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…In general, we found that microbial OTUs clustered according to location and that prokaryotic α diversity was highest in the most pristine site and significantly lower in sites with a history of disturbance. Within the primate clade, similar patterns have been described in the Chlorocebus genus (Trosvik et al, ), Alouatta pigra (Amato et al, ), Lemur catta (Bennett et al, ), and Procolobus gordonorum (Barelli et al, ). GM robustness to habitat disturbance has been reported in parrots ( Strigops habroptilus ; see Perry, Digby, & Taylor, ), but other taxa, including frogs ( Fejervarya limnocharis ; see Chang, Huang, Lin, Huang, & Liao, ), jackals ( Canis mesomelas ; see Menke et al, ), and swan geese ( Anser cygnoides ; see Wu et al, ) show that populations in disturbed habitats exhibit distinct GMs relative to pristine habitat counterparts.…”
Section: Discussionsupporting
confidence: 60%
“…Several studies show that diet plays a crucial role in shaping the GM throughout an individual's life (Clayton et al, ; David et al, ; De Filippo et al, ; Trosvik, Rueness, de Muinck, Moges, & Mekonnen, ; Turnbaugh, Bäckhed, Fulton, & Gordon, ) and over evolutionary timescales (Gomez et al, ; Groussin et al, ; Ley et al, ; Springer et al, ; Trosvik et al, ; Yildirim et al, ). Anthropogenic disturbance is expected to impact food availability in tropical habitats through changes to microclimates that drive variation in species composition (Abbas et al, ; Arrigo‐Nelson, ; Herrera, Wright, Lauterbur, Ratovonjanahary, & Taylor, ).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, in black howler monkeys (Alouatta pigra), seasonal shifts in gut microbiome SCFA production appear to allow hosts to maintain energy balances despite reduced dietary energy intake. [33][34][35] In some cases, these differences reflect losses of microbial taxa, particularly SCFA producers, which may reduce the potential for microbial buffering of host nutritional stress. Although many modern human populations exhibit limited dietary seasonality, evidence of seasonal microbiome dynamics has been reported in some instances.…”
Section: Microbes Buffer Human Nutritional Stressmentioning
confidence: 99%
“…[31,32] Additionally, many primate species exhibit diet-driven differences in gut microbiome composition across habitats. [33][34][35] In some cases, these differences reflect losses of microbial taxa, particularly SCFA producers, which may reduce the potential for microbial buffering of host nutritional stress. [33] Interestingly, species that exhibit this microbial sensitivity to habitat change also have smaller geographic distributions.…”
Section: Microbes Buffer Human Nutritional Stressmentioning
confidence: 99%
See 1 more Smart Citation